Intracellular islatravir pharmacology differs between species in an in vitro model: implications for preclinical study design. (2nd February 2022) - Sykes, Craig; Van Horne, Brian; Jones, Justin; Kashuba, Angela D. M.; Gatto, Gregory; Van Der Straten, Ariane; Johnson, Leah; Cottrell, Mackenzie L.
Abstract: Background: Islatravir (4′-ethynyl-2-fluoro-2′-deoxyadenosine; EFdA) is a first-in-class nucleoside reverse transcriptase translocation inhibitor (NRTTI) being investigated for HIV treatment and prevention. EFdA is intracellularly phosphorylated to EFdA-triphosphate (EFdA-tp), a competitive substrate of deoxyadenosine-triphosphate (dATP). Thus, translating safety and efficacy findings from preclinical studies relies on the assumption that EFdA's intracellular pharmacology can be extrapolated across species. Objectives: We investigated how EFdA is phosphorylated across animal species commonly used for preclinical models in drug development to identify those that most closely matched humans. Methods: PBMCs were isolated from whole blood of six species (human, rhesus macaque non-human primate (rmNHP), rat, minipig, dog, and rabbit) using Ficoll separation and counted on a haemocytometer by Trypan blue staining. One million live cells were cultured in media supplemented with 10 U/mL human IL-2, 10% FBS and 1% antibiotics and treated with 0, 17, 170, and 1700 nM EFdA ( n = 3 replicates per concentration). After 24 h, representative cell counts were derived from untreated control wells (as above), cells were washed in PBS, and lysed with 70:30 methanol:water. EFdA-tp and dATP concentrations were quantified by HPLC-MS/MS and normalized to the representative live cell counts for each species. Results: When compared to human values, EFdA-tp concentrations for each EFdA treatment concentration were lower in all species (rmNHP 1.5–2.1-fold, rat 4.5–15-fold, minipig 37–71-fold, dog and rabbit >100-fold). Additionally, rmNHP and dog PBMCs exhibited significantly higher (7–10-fold; P < 0.001) dATP when compared with human PBMCs. Conclusions: Given intracellular pharmacology differences, these preclinical models may be a conservative estimate of EFdA's intracellular pharmacokinetics and efficacy in humans.